Экспериментальные исследования электротермической стойкости проводов и кабелей к воздействию нормированного по международному стандарту IEC 62305-1-2010 апериодического импульса тока искусственной молнии - Баранов, М.И.; Рудаков, С.В. (Електротехніка і електромеханіка, 2016)
Приведены результаты экспериментальных исследований электротермической стойкости образцов ряда проводов и кабелей электрических цепей объектов промышленной электроэнергетики с медными (алюминиевыми) жилами (экранами), поливинилхлоридной и полиэтиленовой изоляцией к действию короткого удара большого импульсного тока искусственной молнии с нормированными по международному стандарту IEC 62305-1-2010 амплитудно-временными параметрами и допусками на них Приведені результати експериментальних досліджень електротермічної стійкості зразків ряду дротів і кабелів електричних кіл об'єктів промислової електроенергетики з мідними (алюмінієвими) жилами (екранами), полівінілхлоридною і поліетиленовою ізоляцією до дії короткого удару великого імпульсного струму штучної блискавки з нормованими за міжнародним стандартом IEC 62305-1-2010 амплітудно-часовими параметрами і допусками на них. Purpose. Experimental researches of electro-thermal resistibility of cable-explorer products, applied in the power electric circuits of objects of electric-power industry, to action on its copper and aluminum parts bearings a current rationed on the International Standard of IEC 62305-1-2010 aperiodic impulse 10/350 μs of current of artificial lightning. Methodology. Electrophysics bases of technique of high tensions and high pulsed currents (HPC), and also scientific and technical bases of planning of devices of high-voltage impulsive technique and measuring HPC in them. Results. Experimental a way the quantitative levels of maximal values maximum of possible and critical closenesses of aperiodic impulse 10/350 μs of current of artificial lightning with rationed on the international standard of IEC 62305-1-2010 peak-temporal parameters and admittances on them in copper (aluminum) parts bearings a current of send-offs and cables with a polyethylene (PET) and polyvinylchloride (PVCH) isolation. Originality. First in world practice on the unique powerful high-voltage generator of HPC of artificial lightning experimental researches of resistibility to lightning of pre-production models of send-offs (cables) are conducted with copper (aluminum) tendons, PET and PVCH by an isolation, inuse in power electric circuits of electric-power industry objects. Practical value. The use in practice of protecting from lightning of the got results will allow substantially to promote functional and fire-prevention safety of engineering communications of objects of industrial electroenergy in the conditions of action on them of short shots of linear lightning